Synthesis of biodiesel from Jatropha curcas oil using waste eggshell and study of its fuel properties. Issue 78 (26th August 2015) - Chavan, Supriya B.; Kumbhar, Rajendra R.; Madhu, D.; Singh, Bhaskar; Sharma, Yogesh C.
<x xml:space="preserve">Abstract</x> High purity calcium oxide (CaO) was prepared from eggshell and was used as a catalyst for the production of biodiesel.